Estimating the economics and adoption potential of agrivoltaics in Germany using a farm-level bottom-up approach. (October 2022) - Feuerbacher, Arndt; Herrmann, Tristan; Neuenfeldt, Sebastian; Laub, Moritz; Gocht, Alexander
Abstract: This article presents the first bottom-up assessment of the economics and adoption potential of agrivoltaics (AV) using national farm accountancy data in Germany. A recently developed framework for the economic assessment of dual land-use systems is applied to estimate a national AV electricity supply curve. The estimation accounts for economies-of-scale, regional variation in solar radiation, and farm-specific agronomic effects. The results demonstrate that solar radiation and investment costs are key determinants. Agronomic costs from crop shading and land losses have a small impact, but differences between farm-type and regions can be observed. Accounting for economies-of-scale favors farms endowed with large arable land area, which are predominantly specialist field crop and other livestock farm types found in Eastern Germany. In absence of economies-of-scale, early adopters are largely specialist milk or other livestock farm types located in Southern Germany. In presence of economies-of-scale and at an electricity price of 8.3 EUR-cents kWh −1, the 10% most cost-efficient farms could meet 8.8% of Germany's total electricity demand on about 1% of arable land. The results show that substantial policy-support is required to make AV competitive with ground-mounted photovoltaics, particularly if economies-of-scale cannot be realized. Adequate policy designs are needed to safeguard AV's land-efficiency advantage, as most farmers would be incentivized to abandon farming beneath the AV system. Highlights: A national agrivoltaics electricity supply curve is estimated. Economies-of-scale have a strong impact on regional and farm-type specific adoption. 10% most cost-efficient farms meet 9% of electricity demand on 1% of arable land. The break-even price of 8.3 EUR-cents kWh −1 requires substantial policy-support. Adequate policy designs are needed to safeguard AV's land-efficiency advantage.